Analysis of Sociodemographic and Psychosocial Risk Factors for Teenage Pregnancy: A Cross-Sectional Study at The Teen Mom’s Clinic of Mariano Marcos Memorial Hospital and Medical Center Philippines - Liwanto, Michael Adriel; Kristina Vicente Martin; Marriane Grace R. Remolacio (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Teenage pregnancy is a serious public health problem in the Philippines. This study aims to analyze sociodemographic and psychosocial risk factors associated with teenage pregnancy at the Teen Mom's Clinic of Mariano Marcos Memorial Hospital and Medical Center in the Philippines. Methods: A cross-sectional study was conducted on 152 adolescents who consulted at the clinic. Data were collected through a questionnaire that asked about sociodemographic and psychosocial characteristics. Univariate and bivariate statistical analyzes were used to identify risk factors associated with teenage pregnancy. Results: The prevalence of teenage pregnancy among consultation subjects at the clinic was 89%. Bivariate analysis showed that age, place of residence, education level, household income, source of income, parental relationship, sexual relationship, relationship status, source of information about sex, sexual experience, number of sexual partners, contraceptive use, STI information, sexual harassment, physical abuse, and verbal abuse were not significantly associated with teenage pregnancy. Conclusion: Sociodemographic and psychosocial risk factors do not play a significant role in teenage pregnancy in the Philippines.